Comparative analysis of users' awareness and attitudes towards the reference services in academic libraries - Dalina, Daisy S. (2005)
This study was conducted to find out the user's awareness and attitudes towards the reference services of Baliuag University Library and University of Santo Tomas Central Library. This study searched answers to the following questions: (1) Who are the frequent users of the reference section of the library? (1) What are the users' levels of awareness of the reference services? (3) What are the attitudes of the users toward the reference services? (4) What are factors influencing the awareness and attitude of the users toward the reference services offered by the Baliuag University Library and University of the Santo Tomas Central Library? (5) What is the relationship between the age, sex, use of reference section and frequency of use of reference services of the respondents' attitude level? (7) What are the comments/suggestions of the users towards the improvement of the existing reference services in the library?